Bluish‐Green Thermally Activated Delayed Fluorescence Material for Blue‐Hazard Free Hybrid White Organic Light‐Emitting Device with High Color Quality and Low Efficiency Roll‐Off. Issue 9 (17th February 2019) - Wang, Hui; Zang, Chunxiu; Shan, Guogang; Yu, Ziwei; Liu, Shihao; Zhang, Letian; Xie, Wenfa; Zhao, Hongyu
Abstract: High color quality and the removal of blue hazard are important for lighting applications. Thermally activated delayed fluorescence (TADF) materials can achieve ≈100% internal quantum efficiency with low cost. However, it is still challenging to achieve high‐color‐quality and blue‐hazard‐free TADF‐based white organic light‐emitting devices (WOLEDs). Here, a bluish‐green TADF material named 10, 10′‐[5‐(6‐[1, 1′‐biphenyl]‐4‐yl‐2‐phenyl‐4‐pyrimidinyl)‐1, 3‐phenylene] bis [9, 10‐dihydro‐9, 9‐dimethyl‐acridine (DMAC‐BPP) containing two acridines connecting by a phenyl and a pyrimidine is designed and synthesized. Efficient bluish‐green OLED is achieved with DMAC‐BPP emitter. Besides, the yellow and red phosphorescent OLED utilizing DMAC‐BPP as host also shows excellent performance. Thus, a blue‐hazard‐free hybrid WOLED using DMAC‐BPP as host and emitter with maximum external quantum efficiency of 15.6% is achieved. Furthermore, this WOLED shows low efficiency roll‐off and high color quality. Abstract : A bluish‐green thermally activated delayed fluorescence material, DMAC‐BPP, is designed and synthesized to achieve a high‐color‐quality and blue‐hazard‐free white organic light‐emitting device (WOLED). The WOLED achieves maximum EQE of 15.6% and low efficiency roll‐off. It also shows eye‐friendly emission, including a high CRI of 86 and low CCT of 2240 K, meeting the ENERGY STAR requirements for indoor illumination.